INTEGRASI PENDIDIKAN LINGKUNGAN MELALUI PENDKATAN BELAJAR BERSAMA ALAM DI SEKOLAH ALAM QUR’AN BINTANG MADANI - Nadhifa Arufah Chafshah; Yuliyanti; M Eko Juliyansyah; Ali Murtadho; Bakharudin; Ikhsan Mustofa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Amid the deepening global environmental crisis, ecosystem destruction due to human activities, including climate change, pollution, and biodiversity decline, is a major challenge for both current and future generations. In the face of complex environmental problems, environmental education plays an important role in building awareness and concern for natural sustainability. One innovative approach is the integration of environmental education through the "Learning Together with Nature" method, which allows students to not only study theoretically, but also engage directly in natural experiences. This approach teaches the reciprocal relationship between humans and nature and the importance of maintaining ecosystem balance. Through this experience, students can develop a sense of love and responsibility for the environment, collaborate, innovate, and think critically. By integrating environmental education into the curriculum, the younger generation can be prepared to become proactive agents of change in maintaining environmental sustainability. Education plays an important role in shaping future leaders who are aware of the sustainability and importance of preserving nature.